2019
DOI: 10.1038/s41438-019-0215-6
|View full text |Cite
|
Sign up to set email alerts
|

The apricot (Prunus armeniaca L.) genome elucidates Rosaceae evolution and beta-carotenoid synthesis

Abstract: Apricots, scientifically known as Prunus armeniaca L, are drupes that resemble and are closely related to peaches or plums. As one of the top consumed fruits, apricots are widely grown worldwide except in Antarctica. A high-quality reference genome for apricot is still unavailable, which has become a handicap that has dramatically limited the elucidation of the associations of phenotypes with the genetic background, evolutionary diversity, and population diversity in apricot. DNA from P. armeniaca was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
104
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 85 publications
7
104
0
Order By: Relevance
“…We aligned protein sequences from the database UniProt/Swiss-Prot, Arabidopsis thaliana and Prunus persica to each haplotype assembly using the tool Exonerate 43 with the options “--percent 60 --minintron 10 --maxintron 60000”. We mapped RNA-seq reads from reproductive buds, vegetative buds, flowers, leaves, fruits (except seeds) and bark tissues, as well as a published Apricot RNA-seq dataset 23 , using HISAT 44 , and we assembled the transcripts using StringTie 45 . Finally, we used the tool EvidenceModeler 46 to integrate the above evidence in order to generate consensus gene models for each haplotype assembly.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We aligned protein sequences from the database UniProt/Swiss-Prot, Arabidopsis thaliana and Prunus persica to each haplotype assembly using the tool Exonerate 43 with the options “--percent 60 --minintron 10 --maxintron 60000”. We mapped RNA-seq reads from reproductive buds, vegetative buds, flowers, leaves, fruits (except seeds) and bark tissues, as well as a published Apricot RNA-seq dataset 23 , using HISAT 44 , and we assembled the transcripts using StringTie 45 . Finally, we used the tool EvidenceModeler 46 to integrate the above evidence in order to generate consensus gene models for each haplotype assembly.…”
Section: Methodsmentioning
confidence: 99%
“…All genome assemblies, including ‘Rojo Pasion’ haplotypes, ‘Chuanzhihong’ apricot ( Prunus armeniaca ) 23 , Japanese apricot ( Prunus mume ) 25 and ‘Lovell’ peach ( Prunus persica ) 26 , were aligned to each other using nucmer from the MUMmer4 51 toolbox with parameters ‘-max -l 40 -g 90 -b 100 -c 200’. The alignments were further filtered for alignment length (>100 bp) and identity (>90%), with which structural rearrangements and local variations were identified using SyRI 12 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, a 308.06 Mb genome of low-chill Chinese plum 'Sanyueli' with N50 of 815.7 kb was generated. The presence of the majority of BUSCO genes (97.01%) in our assambly indicated that the quality of 'Sanyueli' plum genome is comparable to that of sweet cherry (96.0%) 64 , almond(96.0%) 66 and apricot(98.0%) 68 . The genome size of 'Sanyueli' plum is larger than that of mume 62 , peach 63 , almond 66 and apricot (38.28%) 68 .…”
Section: Discussionmentioning
confidence: 56%